Atezolizumab, Bevacizumab, and Chemotherapy for Newly Diagnosed Stage III or IV Ovarian Cancer: Placebo-Controlled Randomized Phase III Trial (IMagyn050/GOG 3015/ENGOT-OV39). Issue 17 (10th June 2021) - Moore, Kathleen N.; Bookman, Michael; Sehouli, Jalid; Miller, Austin; Anderson, Charles; Scambia, Giovanni; Myers, Tashanna; Taskiran, Cagatay; Robison, Katina; Mäenpää, Johanna; Willmott, Lyndsay; Colombo, Nicoletta; et al.
Abstract : PURPOSE: To evaluate the addition of the humanized monoclonal antiprogrammed death ligand-1 (PD-L1) antibody, atezolizumab, to platinum-based chemotherapy and bevacizumab in newly diagnosed stage III or IV ovarian cancer (OC). METHODS: This multicenter placebo-controlled double-blind randomized phase III trial (ClinicalTrials.gov identifier: NCT03038100 ) enrolled patients with newly diagnosed untreated International Federation of Gynecology and Obstetrics (FIGO) stage III or IV OC who either had undergone primary cytoreductive surgery with macroscopic residual disease or were planned to receive neoadjuvant chemotherapy and interval surgery. Patients were stratified by FIGO stage, Eastern Cooperative Oncology Group performance status, tumor immune cell PD-L1 staining, and treatment strategy and randomly assigned 1:1 to receive 3-weekly cycles of atezolizumab 1, 200 mg or placebo (day 1, cycles 1-22), with paclitaxel plus carboplatin (day 1, cycles 1-6) plus bevacizumab 15 mg/kg (day 1, cycles 2-22), omitting perioperative bevacizumab in neoadjuvant patients. The co-primary end points were investigator-assessed progression-free survival and overall survival in the intention-to-treat and PD-L1–positive populations. RESULTS: Between March 8, 2017, and March 26, 2019, 1, 301 patients were enrolled. The median progression-free survival was 19.5 versus 18.4 months with atezolizumab versus placebo, respectively (hazard ratio, 0.92; 95% CI, 0.79 to 1.07; stratified log-rank P = .28), in the intention-to-treat population and 20.8 versus 18.5 months, respectively (hazard ratio, 0.80; 95% CI, 0.65 to 0.99; P = .038), in the PD-L1–positive population. The interim (immature) overall survival results showed no significant benefit from atezolizumab. The most common grade 3 or 4 adverse events were neutropenia (21% with atezolizumab v 21% with placebo), hypertension (18% v 20%, respectively), and anemia (12% v 12%). CONCLUSION: Current evidence does not support the use of immune checkpoint inhibitors in newly diagnosed OC. Insight from this trial should inform further evaluation of immunotherapy in OC.